Study for Selection Criteria of Two Types Fixed Partial Dentures in Iraqi Population. (Medico Legal Update, 2020)
Fixed prosthodontics is the area of prosthodontics focused on permanently attached (fixed) dental prostheses.The superb esthetic and biocompatible characteristic of ceramic and zirconia restorative materials make boththe most pioneer materials for the construction of the fix prostheses by the dentist. Such dental restoration iscalled direct or indirect restorations according to their method of construction. They include crowns, bridges(fixed dentures), inlays, onlays, and veneers. Prosthodontist is a specialist dentist who have trained to selectthe proper types, material and design of the fixed prostheses. However, comprehensive information aboutthe dental materials are available from the internet websites and social media, which improved the patient’sknowlege and consequently they may share physician in their decision in selecting the tooth reconstructionmaterials. The current survey study concerned three factors that may affect patient’s choice for the fixprostheses: (1) internet information, (2) doctor advice, (3) the cost. A total of 100 patients who attending theclinic of the Operative Dentistry in the last 16 months for aesthetic restorations were included in the survey.The samples included 72 female and 28 males of age ranged between 30 and 69 years. The survey basedon the criteria for selection the type of fixed metal according to the following items,(1) internet and socialmedia information’s, (2) advice of doctor, and (3) the price. The results showed that 67 of patient’s choosezircon while 33 of them choose porcelain fused to metal. Furthermore, the results revealed that the internetrepresented 36% of selection criteria chosen for this study, compared to 34% due to doctor advice and 30%.Due to cost of the treatment The P value were